Easy Access to Isomeric 7-Deazapurine–1,2,3-Triazole Conjugates via SNAr and CuAAC Reactions of 2,6-Diazido-7-deazapurines - Bucevicius, Jonas; Turks, Maris; Tumkevicius, Sigitas (Synlett, 2018)
A simple and efficient synthesis of isomeric 7-deazapurine–1,2,3-triazole conjugates with amino substituents from readily available 9-alkyl-2,6-diazido-7-deazapurines has been developed using consecutive CuAAC and regioselective nucleophilic substitution reactions of azido and 1,2,3-triazole groups with amines.
Keywords: heterocycles; 7-deazapurines; triazoles; click chemistry; nucleophilic aromatic substitution; regioselectivity